Creep and resilient modulus properties of asphaltic concrete containing black rice husk ash - Putra Jaya, Ramadhansyah; Haryati, Yaacob; Norhidayah, A. H.; Mohd Rosli, Hainin; Muhammad Naqiuddin, Mohd Warid; Azman, Mohamed; Abdul Rahim, A. H.; Ekarizan, S. (IOP Science, 2019)
Black rice husk ash (BRHA) is one of the agro-waste that could be used to improve the properties of asphalt mixture. In this investigation, the BRHA was grounded using a laboratory ball mill with porcelain balls to fine particles size less than 76 μm. Four different BRHA contents were considered in this study namely 0%, 2%, 4% and 6% by weight of binder. The performance of asphaltic concrete containing BRHA was evaluated through resilient modulus and dynamic creep test. It was found that the BRHA can be satisfactorily used as a filler material in order to increase the properties of creep and stiffness modulus asphaltic concrete. Test results also indicate that asphaltic concrete containing 2% to 4% BRHA showed excellent performance to resilient modulus and dynamic creep properties.